Analisis Survei Kepuasan Masyarakat Pada Mal Pelayanan Publik (MPP) Kota Batam - Ohan Suryana (Puslatbang KHAN, 2019)
The writing of this article aims to determine the extent of service user satisfaction at the Batam city public service mall. This study uses a quantitative descriptive approach. Analysis of data using survey methods with SPSS 25 program. Methods of data collection using a questionnaire with a Likert scale. The validity test results of the r results are above 0.195 (r table) so it can be concluded that the research statement is valid. The reliability test results show Alpha value of 0.955 while the constant value is 0.6, so the overall statement is declared reliable. The results showed that service users from each dimension or element included: requirements, system, time, cost, specification of service type, implementing competency, implementing behavior, complaint handling and facilities and infrastructure expressed satisfaction with the services provided by the Public Service Mall Batam city.